Faktor Ibu Yang Ada Hubungan Dengan Kejadian Preeklampsia Pada Ibu Hamil Di Beberapa Lokasi Di Wilayah Indonesia Periode Tahun 2014 Sampai dengan Tahun 2021 - Tandiarrang , Jelita Pristika; Murnita , Ika Azdah; Dwirosalia NS, Desi (Bosowa Medical Journal, 2025)
Preeclampsia is a pregnancy-specific syndrome with decreased organ perfusion resulting in vascular vasospasm and vascular activation. To determine the relationship between maternal factors and the incidence of preeclampsia in pregnant women in several locations in Indonesia from 2014 to 2021. The research method used in this research is a systematic review method with a case control approach, using research journals on preeclampsia in pregnant women in several locations in Indonesia from 2014 to 2021, which aims to determine the relationship between maternal risk factors and the occurrence of preeclampsia. The results of the seventeen research journals analyzed showed that there was a maternal factor that had a relationship with the incidence of preeclampsia in pregnant women in several locations in Indonesia, namely that there was a significant relationship between parity status (p value 0.000), body mass index (p value 0.000), multiple pregnancy (p value 0.000), history of preeclampsia (p value 0.000). The conclusion is that the causes of maternal factors are related to the incidence of preeclampsia in pregnant women in several locations in Indonesia for the period 2014 to 2021, there are parity status, body mass index, multiple pregnancies, history of preeclampsia